PERLINDUNGAN HUKUM TERHADAP ANAK DI BAWAH UMUR DALAM UPAYA MENGEMBANGKAN KUALITAS SUMBER DAYA MANUSIA LEGAL PROTECTION ON CHILDREN UNDER THE AGE QUALITY EFFORTS IN DEVELOPING HUMAN RESOURCES - Abdikoro, HM (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2010)
The analysis of the early marriage in regards to the law with the protection  of the under age child towards the development of the quality of human resources, that the results of this research was qualified as. the legal research  that wasnter and multi disciplinary, so as the source of the  data that came from  the bibliography  research,  was supported  by results  of field  work  through  the interview. The data was gathered to be analyzed through the juridical analysis method  quantitative  by  depicting the  data in accordance  with  the problem henceforth was interpreted, systemized, as well as was given  by the argumentation to get the conclusion. Results of the  research showed  evidently the lower age limit for  the woman to be married resulted in the rate of the birth being higher, also showed the existence of the life in the household not harmonious. In the implementation of the marriage, the manipulation of the age, without the courts dispensation happened. Factors that affected it in part, the free  association, the culture the tradition,   education,   economics,  as  a  result  the  development  of   human resources  was doubted,  become more  immature, often  quarrelling,  the  high divorce, and often were being sick. The child was forced  to drop out of school, the child lost the cheerful life in the childhood, and hindered to psychological development the   identity  of the child  was forced  to become fast  mature  as adult. In  connection   with  that  then  marriage   regulations   of  the  number 1 in  1974 determined   the age  limit  to be  married,   the man  in  19 years  old  whereas  the woman  is 16 years  old. 1